The impact of educational leadership in improving the learning experience - Culduz, Murat (IGI Global, 2024)
Education is a fundamental pillar of society, and the quality of educational leadership plays a crucial role in shaping the learning experience for students. Educational leaders, such as principals and school administrators, have the power to influence and transform educational environments. This study aims to explore the impact of educational leadership on improving the learning experience. It delves into the various dimensions of effective educational leadership, including instructional leadership, organizational management, and creating a positive school culture. By examining the research and best practices in educational leadership, this study seeks to shed light on how strong leadership can enhance teaching and learning, promote student engagement and well-being, and ultimately lead to improved learning outcomes.
Keywords: School Leadership; Case Study; Leadership in Education